Emerging reproductive technologies and the legitimization of reproductive futures: the ontological choreography of in vitro gametogenesis - Alberto Aparicio; Hannah Carpenter (New Genetics and Society)
The expansion of biotechnology's frontiers include in vitro gametogenesis (IVG), which allows the generation of gametes from pluripotent stem cells. By analyzing discourses from two IVG companies – Conception and Ivy Natal – the authors examine the framing of IVG as a continuation of normalized IVF practices and a revolutionary reproductive technology. The paper suggests that IVG proponents engage in “ontological choreography” to integrate their technology into existing accepted reproductive frameworks while simultaneously mobilizing liberatory arguments emphasizing reproductive autonomy, expanded reproductive access, and genetic kinship. The authors highlight tensions in how IVG is temporally framed within idealized futures of expanded reproductive access. The paper also examines a workshop organized by the National Academies of Science, Engineering, and Medicine in 2023, illustrating how commercial actors selectively engage with ethical arguments in ways that narrow the complexity of issues at stake. The authors conclude with the need for enhanced public deliberation regarding IVG's trajectory.